Optimizing vaccine allocation for COVID-19 vaccines shows the potential role of single-dose vaccination - Laura Matrajt (Nature Portfolio, 2021)
Most COVID-19 vaccines require two doses but a single dose provides partial protection, so it is unclear how best to prioritize vaccine distribution in the context of limited supply. Here, the authors show that campaigns in which some age groups receive one dose while others receive both doses may be optimal.